Intrinsic and Extrinsic Thymic Adrenergic Networks: Sex Steroid-Dependent Plasticity - Leposavić, Gordana Momčilo; Pilipović, Ivan M. (Frontiers in Endocrinology, 2018)
The thymus is sexually differentiated organ providing microenvironment for T-cell precursor differentiation/maturation in the major histocompatibility complex-restricted self-tolerant T cells. With increasing age, the thymus undergoes involution leading to the decline in efficacy of thymopoiesis. Noradrenaline from thymic nerve fibers and “(nor)adrenergic" cells is involved in the regulation of thymopoiesis. In rodents, noradrenaline concentration in thymus, and adrenoceptor expression on thymic cells, depend on sex and age. These differences are suggested to be implicated in the development of sexual diergism and the age-related decline in thymopoiesis. The programming of both thymic sexual differentiation and its involution occurs during the critical early perinatal period, and may be reprogrammed during peripubertal development. The thymic (re)programming is critically dependent on circulating levels of gonadal steroids. Although the underlying molecular mechanisms have not yet been elucidated fully, it is assumed that the gonadal steroid action during the critical perinatal/peripubertal developmental periods leads to long-lasting changes in the efficacy of thymopoiesis partly through (re)programming of “(nor)adrenergic” cell networks and adrenoceptor expression on thymic cells.